Evaluation of multimedia programs in sport science education - Wiemeyer, J. (International Journal of Computer Science in Sport, 2003)
When developing multimedia as an educational tool, formative and summative evaluations should be applied. Among other aspects, these evaluations can pertain to the extent and way of use, the learning contents and their formal presentation, the learning results, the acceptability, and the usability of the multimedia tool. Furthermore, effectivity and efficiency of the multimedia program can be examined. Several qualitative and quantitative tools can be applied, e.g., expert evaluation according to specific models of cognition, perception and action, discussions and interviews with users, observation of users in real-life or laboratory situations, heuristic evaluation, using paper or electronic prototypes, or scenario techniques. Three multimedia tools for education are currently developed: - Program EidS for introduction to studying sport sciences. - Program BWS-CBT for introduction to movement science. - Program BioPrinz for introduction to the principles of biomechanics. During the development process the following research methods have been applied: - thinking aloud - qualitative interviews - three questionnaires (ISO norm 9241/10 and IsometricsL questionnaires, selfdeveloped multimedia questionnaire) - logs documenting the experiences with the actual use of the program The results of the evaluations clearly confirm the efficiency of qualitative methods as means for formative evaluation.